Exploring Students’ Anxiety in Online and Offline English Language Classrooms - Stefanus Prima; Budi Riyanto; Dang Hartono (ITScience (Information Technology and Science), 2022)
This study investigates the Foreign Language Classroom Anxiety Score (FLCAS) of students in English classes before the pandemic (offline class) and during the COVID-19 pandemic (online class) in a private university in Jakarta, Indonesia. There were 145 participants in total, 67 of which attended the offline class of English 1, while 78 others attended the online class of English 2. The 33 items of the questionnaire were adapted from FLCAS and were analyzed by three aspects: Communication Apprehension, Fear of Negative Evaluation, and Test Anxiety. The questionnaire items were translated into Indonesian and distributed online using Survey Monkey. The study used Independent Samples t-test to test the hypothesis, and the writer analyzed items to categorize the FLCA scores into high and low anxiety levels of each anxiety category. The writer found the FLCAS difference between offline and online classes insignificant (p > 0.05). Furthermore, The writer revealed that Fear of Negative Evaluation, especially judgment from classmates, was the dominant aspect that caused anxiety among students of both classes. On the other hand, it was also found that learners from both classes had no problem having their teacher correct their errors when using English.